Broken mouldings with diamond designs inside the boundary wall of the temple - Temples of India Project Team (Jio Institute, 2024)
A row of broken mouldings with diamond designs is kept, inside the boundary wall, in the Neelkanth Mahadev Temple premises. These portions must have been part of the original plinth of the temple.